The Expediency Principle of Inanimate Land: a Study of Ihya' al-Mawat in Classical Fiqh and Land Reform in Indonesian Agrarian Law - Wahyuni, Sri (Al-Mazaahib: Jurnal Perbandingan Hukum, 2024)
This article examines the comparison between the fiqh concept of iḥyā' al-mawāt and Indonesian national agrarian law on land reform, especially the right to open land. The author uses a comparative approach in this discussion, which compares the existing concepts in fiqh (as Islamic law) and national agrarian law (as Indonesian positive law). This article contributes to the discourse on Islamic land law, also known as agrarian fiqh, which has not been widely studied. This article shows that in the classical Islamic literature, there has been a study of land and how the Prophet Muhammad PBUH regulated land management. One of the concepts in fiqh is iḥyā' al-mawāt, which is to revive dead land. This is a starting point to introduce the tradition of agrarian fiqh in the classical literature. This article concludes that in both fiqh and Indonesian agrarian law, there is a concept of land clearing based on the principle of expediency. However, iḥyā' al-mawāt and the Indonesian national agrarian law on land reform still have differences, both in terms of concept, regulation, and implementation. This article is limited to a literature review that must be further studied from the context of the application of these two laws. This article contributes to the understanding of the two laws that are applied in Indonesia, namely positive law and Islamic law.   Artikel ini mengkaji tentang perbandingan antara konsep fiqh tentang iḥyā’ al-mawāt dan hukum agraria nasional Indonesia tentang land reform, terutama hak membuka lahan. Penulis menggunakan pendekatan perbandingan dalam pembahasan ini, yaitu membandingkan konsep yang ada dalam fiqh (sebagai hukum Islam) dan hukum agraria nasional (sebagai hukum positif Indonesia). Artikel ini memberikan kontribusi tentang wacana hukum pertanahan Islam atau dapat juga disebut sebagai fiqh agraria yang belum banyak dikaji. Artikel ini menunjukkan bahwa dalam khazanah Islam klasik telah dikenal kajian tentang tanah dan bagaimana Nabi Muhammad saw. mengatur tentang pengelolaan tanah. Salah satu konsep dalam fiqh adalah iḥyā’ al-mawāt, yaitu menghidupkan tanah mati. Hal ini menjadi satu titik awal untuk memperkenalkan tradisi fiqh agraria dalam khazanah klasik. Dari artikel ini dapat diambil kesimpulan bahwa baik dalam fiqh maupun dalam hukum agraria Indonesia terdapat konsep tentang membuka lahan yang berdasarkan asas kemanfaatan. Dalam fiqh dikenal dengan istilah iḥyā’ al-mawāt dan dalam hukum agraria dikenal adanya hak membuka lahan. Namun demikian, iḥyā’ al-mawāt dan hukum agraria nasional Indonesia tentang land reform tetap memiliki perbedaan, baik dari segi konsepnya, pengaturannya, maupun dari segi pelaksanaannya. Artikel ini sebatas kajian Pustaka yang harus dilanjutkan kajiannya dari aspek implementasi dua hukum tersebut. Artikel ini berkontribusi pada pemahaman dua hukum yang berlaku di Indonesia, yaitu hukum positif dan hukum Islam.